A framework for priority setting in international livestock research - Randolph, Thomas F.; Kristjanson, Patricia M.; Omamo, Steven Were; Odero, A.N.; Thornton, Philip K.; Reid, Robin S.; Robinson, Timothy P.; Ryan, J.G. (Oxford University Press, 2001)
Priorities are assessed according to: the contribution of the proposed research to poverty alleviation; expected economic and environmental impacts; internationality of the problem and solution; and contribution to capacity building and improved research efficiency. A weighted composite index is then derived. The framework allows Monte Carlo sampling of probability distributions imputed to uncertain input variables. Resultant probability distributions can then be compared to assist in selecting efficient candidate research themes. Use of the framework is illustrated with respect to research themes that may be undertaken by ILRI and partners. Results confirm the importance of a portfolio approach to priority setting.